(untitled) (Journal of Parents and Teachers, 2014)
In this article, the author addresses the subject of forgiveness, pointing out that it is a task that is poorly assimilated by a large part of society. For this reason, she presents six lessons in which she condenses the essential aspects behind the human capacity to forgive.